El Greco, pintor culto y poeta para los ojos: sobre Pacheco, Góngora, el Laocoonte y la Vista y plano de Toledo - Héctor Ruiz Soto (Mélanges de la Casa de Velázquez, 2025)
In 1646, Faria e Sousa described El Greco as “the Statius and the Góngora of poets for the eyes.” This comparison between the painter and the poet arose on the margins of the Gongorist controversy, and can be understood through its intersection with another debate, quieter yet significant: Francisco Pacheco’s dispute with El Greco over the scientific nature of painting. In practice, this second controversy revolves around El Greco’s dual reputation—as both brilliant and extravagant, particularly in his theoretical views, as he resisted the formalisation of painting as an Art. The documents linked to this debate, examined alongside two of the Cretan artist’s masterpieces, Laocoön and View and Plan of Toledo, support our argument for regarding El Greco as an erudite painter, a culto. Here, we use the term in a sense akin to its meaning in contemporary poetry, drawing a parallel with Góngora’s poetics and the shifting tides of his reputation.